Some Remarks to the Semantics of Image of Deity on the Coffin of Sepi III (Cairo CG 28083). - Tarasenko, Mykola (Eikón / Imago, 2021)
The problem of the iconography of a unique image of a deity drawn on the Middle Kingdom rectangular coffin of Sepi III (Cairo CG 28083; B1C; Deir el-Bersha; CT VI, 386) is discussed in the article. It is possible that the god is the first known image of the syncretic double god Re-Osiris. The deity (with a head unusually for Egyptian iconography unfolded in full face) is shown sitting on a throne with the inscription “millions (of years)”. The image of this god could be a visual display of the eschatological plot described in Spell 1130 of the Coffin Texts (the union of Atum(-Re) and Osiris after destruction of the Universe) at the end in the Book of Two Ways, that is represented on the bottom of Sepi’s coffin.